Synthesis of CoIICoIII 2-xAlxO4-Al 2O3 nanocomposites via decomposition of CoII 0.73CoIII 0.27(OH) 2.00(NO3)0.23(CO3) 0.02·0.5H2O in a sol-gel-derived γ-Al2O3 matrix - Sampanthar, J.T. (2014)
10.1021/cm010553o